Inequality in modern contraceptive use and unmet need for contraception among women of reproductive age in Zambia. A trend and decomposition analysis 2007–2018 - Joseph Kazibwe; Felix Masiye; Marie Klingberg-Allvin; Björn Ekman; Jesper Sundewall (Reproductive Health)
Abstract Background Access to contraception can be a transformational intervention towards advancement of education, health, and freedom of choice. Countries have committed to improving access to contraception enshrined in the sustainable development goals (SDGs), indicator 3.7.1. Our study seeks to investigate the level of inequality in current use of modern contraception and unmet need for contraception among sexually active women of reproductive age in Zambia during 2007, 2013/14 and 2018 to inform family planning policy. Methods We use three rounds of Zambia demographic and health survey datasets for the years 2007, 2013/14 and 2018, which are nationally representative surveys. We included a total of 19,973 sexually active women of reproductive age from 15 to 49 years living in Zambia. The level of inequality was assessed using concentration curves, and indices. The concentration indices were decomposed to identify the causes of the inequality. Results Our analysis shows that there was inequality in the current use of modern contraception across the years 2007, 2013/14 and 2018. The concentration curves showed that current use of modern contraception was higher among the wealthy than the poor. This pro-rich trend was consistent throughout the study period. Erreygers concentration Index (EI) values were 0.2046 in 2007, 0.1816 in 2013/14, and 0.1124 in 2018. The inequality in current use of modern contraception was significantly influenced by having access to contraceptive counselling, education level and being in a union (living with a partner). In addition, there was inequality in unmet need for contraception with concentration curves showing that unmet need for modern contraception was experienced more among the poor compared to the wealthy. Unmet need was thus pro poor. The EI values were – 0.0484 in 2007, – 0.0940 in 2013/14 and – 0.0427 in 2018. This inequality was significantly influenced by education, employment status, being in a union, and having health insurance. Conclusion Inequality in modern contraceptive use and unmet need for contraception exists and has persisted over the years in Zambia. Such inequality can be addressed through a multipronged approach that includes encouraging women to visit health facilities, access to contraceptive counselling, and promoting formal education.